The choice of precursors in the synthesizing of CuMnOx catalysts for maximizing CO oxidation - Dey S.; Dhal G.C.; Mohan D.; Prasad R. (My University, 2025)
The hopcalite (CuMnOx) catalyst is a well-known catalyst for CO oxidation at a low temperature and it is synthesized by the co-precipitation method with different types of precursors. Activity of the CuMnOx catalysts for CO oxidation is strongly dependent upon the combination of precursors, ranking in order {Mn(Ac)2 + Cu(NO3)2} > {Mn(Ac)2 + Cu(Ac)2} > {Mn(NO3)2 + Cu(NO3)2} > {Mn(NO3)2 + Cu(AC)2}. All the precursors were precipitated by KMnO4 solution and the precursors mostly comprised of MnO2, Mn2O3 and CuO phases. Keeping the same precipitant while changing the precursors caused a change in the lattice oxygen mobility which influenced the CO oxidation activity. The calcination strategy of the precursors has great influence on the activity of resulting catalysts. The reactive calcination (RC) conditions produce multifarious phenomena of CO oxidation and the precursor decomposition in a single-step process. The activity order of the catalysts for CO oxidation was as follows: reactive calcination (RC) > flowing air > stagnant air. Therefore, we recommended that the RC route was the more appropriate calcination route for the production of highly active CuMnOx catalysts. All the catalysts were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, Brunauer–Emmett–Teller analysis, X-ray photoelectron spectroscopy and scanning electron microscopy technique. The influence of precursors on the structural properties and the catalytic activity of co-precipitation derived binary CuMnOx catalysts for CO oxidation has been investigated. © 2018, The Author(s).